2019
DOI: 10.3390/bs10010008
|View full text |Cite
|
Sign up to set email alerts
|

Why Do We Watch? The Role of Emotion Gratifications and Individual Differences in Predicting Rewatchability and Movie Recommendation

Abstract: Background: The present study’s main aim was to determine the predictors of movie rewatchability and recommendations. Methods: Using a sample of 318 participants, we first tested the structure of a gratification scale from watching a movie. Then, we examined the role of age, need for cognition, need for affect, extraversion, and emotional gratifications, in predicting individuals’ interest in rewatching the movie and in making recommendations. Results: As in the original proposal of the emotional gratification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…NFA prediction has comprehensive applications. As individuals with different NFA prefer different types of services and products, e.g., movies (23) and product brands (19), understanding consumers' NFA is helpful for businesses to recommend and provide more user-friendly products. Based on the conclusion that NFA has a significant relationship with some mental health symptoms and suicidal tendencies (3)(4)(5)(6)(7)(8), NFA prediction could help mental health workers provide more efficient and effective mental health services, including large-scale mental health monitoring and novel suicide interventions.…”
Section: The Possible Implications Of Nfa Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…NFA prediction has comprehensive applications. As individuals with different NFA prefer different types of services and products, e.g., movies (23) and product brands (19), understanding consumers' NFA is helpful for businesses to recommend and provide more user-friendly products. Based on the conclusion that NFA has a significant relationship with some mental health symptoms and suicidal tendencies (3)(4)(5)(6)(7)(8), NFA prediction could help mental health workers provide more efficient and effective mental health services, including large-scale mental health monitoring and novel suicide interventions.…”
Section: The Possible Implications Of Nfa Predictionmentioning
confidence: 99%
“…NFA could help to explain individuals' differences in many critical mental aspects such as mental health (3)(4)(5)(6)(7)(8)(9), information preferences and decision making (10)(11)(12)(13)(14), social attitude [e.g., evaluation of self and others (15)(16)(17)(18), attitudes toward brands (19), attitudes toward job (20), attitudes toward the country (21), drugs (22)] and so on. It has also been found that NFA influences individual reactions to media and entertainment (23,24), political beliefs and ideology (16,25), legal decisions (26) and risk taking capacity (27).…”
Section: Introductionmentioning
confidence: 99%
“…Applying this idea to movies, Bartsch [24] extended previous mood management theories, arguing that the emotional gratification, extracted from watching a movie, comes from both enjoyment and the satisfaction of social and cognitive needs. Using Bartsch model, recent studies have shown the importance of the type of gratification that usually motivates a person to watch a movie in predicting her/his own interest in watching and recommending a particular movie to another person [25,26]. For example, in the study of Piçarra et al [26], participants with higher hedonic motives reported more interest for a movie that was previously evaluated as displaying hedonic content, whereas those reporting eudaimonic motives were more interested in a movie evaluated as having eudaimonic content.…”
Section: Movies Emotions and Meaningmentioning
confidence: 99%
“…1 Repeated watching becomes easy to achieve, given the advances in digital technologies and networking, allowing individuals to access movies or TV series in a more affordable way. 2 There are some professional video applications, such as Tencent Video, iQIYI Video, and Youku Video, in China. In particular, Youku Video has bought the copyrights of COMTS, making these people more easily recall and relive specific moments in media episodes.…”
Section: Introductionmentioning
confidence: 99%